2018
DOI: 10.1093/jas/sky420
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlations among weight and cumulative productivity of crossbred beef cows1

Abstract: Mature weight of beef cows in the United States has been increasing as a correlated response to selection for calf growth. Unfavorable genetic correlations between cow weight and various measures of female fertility, stayability, and lifetime production suggest declining cow productivity might also be expected as a correlated response to growth selection. National cattle evaluations, however, show increasing trends for stayability and sustained fertility. Random regression (RR) models were employed to further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 59 publications
3
12
0
1
Order By: Relevance
“…Heritability (h 2 ) estimates in the present study are in line with what is generally reported in the literature (Kitchenham and Rowlands, 1976;Bourdon and Brinks, 1982;Rowlands et al, 1983;Arnold et al, 1991;Bullock et al, 1993;Bennett and Gregory, 1996;Phocas and Laloë, 2004;Wright et al, 2014;Mpetile et al, 2015;Snelling et al, 2019). Heritability estimates (h 2 ) for white blood cell traits by Leach et al (2013) ranged from 0.28 to 0.50, confirming the findings of the present study, with the only exception of MO which had a heritability estimate (h 2 ) of 0.11 and 0.01 for Bayesian and frequentist approaches respectively, which in both cases are lower than the estimates previously reported by Leach et al (2013) that ranged from 0.21 to 0.39.…”
Section: Blood-based Traits Tend To Have Moderate To High Heritabilitysupporting
confidence: 92%
“…Heritability (h 2 ) estimates in the present study are in line with what is generally reported in the literature (Kitchenham and Rowlands, 1976;Bourdon and Brinks, 1982;Rowlands et al, 1983;Arnold et al, 1991;Bullock et al, 1993;Bennett and Gregory, 1996;Phocas and Laloë, 2004;Wright et al, 2014;Mpetile et al, 2015;Snelling et al, 2019). Heritability estimates (h 2 ) for white blood cell traits by Leach et al (2013) ranged from 0.28 to 0.50, confirming the findings of the present study, with the only exception of MO which had a heritability estimate (h 2 ) of 0.11 and 0.01 for Bayesian and frequentist approaches respectively, which in both cases are lower than the estimates previously reported by Leach et al (2013) that ranged from 0.21 to 0.39.…”
Section: Blood-based Traits Tend To Have Moderate To High Heritabilitysupporting
confidence: 92%
“…Cow weight at pregnancy test (CW) and cumulative weight weaned (WtW) records were obtained on 6211 genotyped females from GPE Cycles VII [ 18 ] and VIII [ 19 ] and the current 18-breed continuous GPE sampling [ 20 ], following procedures developed for random regression analyses of these traits [ 9 ]. Briefly, a record for WtW was created each time a female was exposed to breeding, starting with their initial breeding to calve as a two-year-old.…”
Section: Methodsmentioning
confidence: 99%
“…The extension of stayability to evaluate cow weight and cumulative cow productivity [ 9 ] under a restricted breeding season provides refined tools to breed for sustainability. These evaluations predict the most and least productive cows, and weight indicates feed requirements [ 10 ] and methane emissions [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longevity is the most important functional trait in cattle selection worldwide [6]. There are previous works where they show negative correlations between the weight of the cow and the stability or the useful life of the same; this made that the main associations of meat breeds in the USA report on the permanence or fertility of cows [7]. Some of the fertility measures used in beef cow evaluations, such as length of productive life, interval between the first and second calving, and calves born at a specific age, should be incorporated into analyses of the entire life of the cow [8].…”
Section: Introductionmentioning
confidence: 99%